2006
DOI: 10.1134/s0006297906090070
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of activation of cytochrome c peroxidase activity by cardiolipin

Abstract: In this work, the actions of bovine heart cardiolipin, synthetic tetraoleyl cardiolipin, and a nonspecific anionic detergent sodium dodecyl sulfate (SDS) on cytochrome c (Cyt c) peroxidase activity recorded by chemiluminescence in the presence of luminol and on the Fe...S(Met80) bond whose presence was estimated by a weak absorption band amplitude with peak at 695-700 nm (A(695)) were compared. A strict concurrency between Fe...S(Met80) breaking (A(695)) and cytochrome peroxidase activity enhancement was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…Peroxidase activity increases significantly when the protein is partially unfolded or the Met80-Fe bond is weakened or ruptured by exposure to CL. 27,34 Our studies suggest that SS-31 prevents CL from breaking the Met80-Fe coordination in cyt c. A proposed model for this mechanism is illustrated in Figure 9B. Unlike other inhibitors of cyt c peroxidase that have been described, [49][50][51][52] SS-31 is selectively targeted to CL rather than the mitochondrial matrix and does not alter CL composition or the normal interaction between CL and cyt c.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Peroxidase activity increases significantly when the protein is partially unfolded or the Met80-Fe bond is weakened or ruptured by exposure to CL. 27,34 Our studies suggest that SS-31 prevents CL from breaking the Met80-Fe coordination in cyt c. A proposed model for this mechanism is illustrated in Figure 9B. Unlike other inhibitors of cyt c peroxidase that have been described, [49][50][51][52] SS-31 is selectively targeted to CL rather than the mitochondrial matrix and does not alter CL composition or the normal interaction between CL and cyt c.…”
Section: Discussionmentioning
confidence: 77%
“…22,33 We found that Ca 2+ directly stimulates cyt c peroxidase activity in a dose-dependent manner ( Figure 2E), and SS-31 inhibited Previous studies suggest that the insertion of a CL acyl chain into the heme crevice of cyt c disrupts the Met80-Fe coordinate and exposes the heme Fe. 34,35 Disruption of the Met80-Fe ligation can be monitored by circular dichroism (CD). 36,37 The addition of CL to cyt c resulted in the loss of the negative Cotton peak at 419 nm and was prevented by the addition of SS-31 in a 1:1 ratio with cyt c ( Figure 3B).…”
Section: Cl-induced Cyt C Peroxidase Activitymentioning
confidence: 99%
“…We used luminol-dependent CL for studies of peroxidase activity of cytochrome c associated with cardiolipin [7]. The kinetics of CL (initial elevation of fluorescence and its subsequent drop) confirms Fig.…”
Section: Activated CLmentioning
confidence: 67%
“…Cardiolipin specifically potentiated the initially low peroxidase activity of cytochrome c many times stronger than free fatty acids or anionic detergents. Activation of the cytochrome c peroxidase activity is now regarded as the initial stage of apoptosis [7].…”
Section: Activated CLmentioning
confidence: 99%
See 1 more Smart Citation